Analysis and Numerical Solution of Transient Electromagnetic Scattering from Overfilled Cavities (Communications in Computational Physics, 2020)
A hybrid finite element (FEM) and Fourier transform method is implemented to analyze the time domain scattering of a plane wave incident on a 2-D overfilled cavity embedded in the infinite ground plane. The algorithm first removes thetime variable by Fourier transform, through which a frequency domain problem is obtained. An artificial boundary condition is then introduced on a hemisphere enclosingthe cavity that couples the fields from the infinite exterior domain to those inside. Theexterior problem is solved analytically via Fourier series solutions, while the interiorregion is solved using finite element method. In the end, the image functions in frequency domain are numerically inverted into the time domain. The perfect link overthe artificial boundary between the FEM approximation in the interior and analyticalsolution in the exterior indicates the reliability of the method. A convergence analysisis also performed.